Neinvazivnye metody opredelenija laktatnogo poroga v podgotovke begunov-studentov - Kryazhev, V. D.; Volodin, R. N.; Solovyov, V. B.; Skudnov, V. M. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
The purpose of this study is to determine the suitability of non-invasive field tests of anaerobic threshold estimation for use in training students, middle distance runners. Twelve runners in the 19-22 age average with a 1500 m personal best 4.02,3-4.34,2 minute were tested in the laboratory to determine the lactate threshold. The athletes then completed two field tests: a 3000 m run and Conconi test to predict running speed values at the lactate threshold level based on test results. The high level of correlation (r = 0.95) between distance time and lactate speed obtained in the laboratory (exp-Dmax method) allowed to build equations of linear regression of the relationship of the lactate threshold with the results of the control run at 3000 m. The ratio is determined by the formula: LTDmax = 10.22 - 0.0115×?3000 (m/sec). The results of the study suggest that the method of estimation the lactate threshold based on the results of running for 3 km can be recommended to trainers and midle and long distances runners as a method of estimation lactate threshold - the criterion of intensity training loads.